The effect of swinging the arms on muscle activation and production of leg force during ski skating at different skiing speeds - Göpfert, C.; Lindinger, St. J.; Ohtonen, O.; Rapp, W.; Müller, E.; Linnamo, V. (Human Movement Science, 2016)
The study investigated the effects of arm swing during leg push-off in V2-alternate/G4 skating on neuromuscular activation and force production by the leg muscles. Nine skilled cross-country skiers performed V2-alternate skating without poles at moderate, high, and maximal speeds, both with free (SWING) and restricted arm swing (NOSWING). Maximal speed was 5% greater in SWING (P < 0.01), while neuromuscular activation and produced forces did not differ between techniques. At both moderate and high speed the maximal (2% and 5%, respectively) and average (both 5%) vertical force and associated impulse (10% and 14%) were greater with SWING (all P < 0.05). At high speed range of motion and angular velocity of knee flexion were 24% greater with SWING (both P < 0.05), while average EMG of m. biceps femoris was 31% lower (all P < 0.05) in SWING. In a similar manner, the average EMG of m. vastus medialis and m. biceps femoris were lower (17% and 32%, P < 0.05) during the following knee extension. Thus, swinging the arms while performing V2-alternate can enhance both maximal speed and skiing economy at moderate and, in particularly, high speeds.